Tuning up the photovoltaic performances upon the utility of diketopyrrolopyrrole in PEO-based gel polymer electrolytes. Issue 22 (11th May 2021) - Kumar, Sanath; Panigrahi, Pranshula; Mohanty, S.; Nayak, S. K.; Palai, Akshaya Kumar
Abstract : Schematic illustration of the electron transfer mechanism taking place in the fabricated DSSC with PEO/DPP-H/PC/TPAI/KI/I 2 gel electrolyte. Abstract : The role of diketopyrrolopyrrole (DPP-H) as an additive on the ionic conductivity of poly(ethylene oxide) (PEO)-based gel polymer electrolytes (GPE) was studied for DSSC applications. The pure PEO/PC/KI/TPAI/I2 GPE was prepared with a mixture of propylene carbonate (PC) as a non-volatile plasticizer and iodide salts, such as potassium iodide (KI), tetrapropylammonium iodide (TPAI) and iodine (I2 ), together with PEO. The modified GPEs were prepared with different weight percentage (wt%) ratios (0.5%, 0.75%, 1% and 1.25%) of DPP-H using acetonitrile as a solvent. The polymer gel electrolytes were characterized by X-ray diffractometer (XRD) and Fourier transform infrared spectroscopy (FTIR), and the electrochemical properties were analyzed to relate the nature of the polymer and iodine ion conducting properties. The pure PEO/PC/TPAI/KI/I2 electrolyte exhibited an ionic conductivity value of 0.084 mS·cm −1 at room temperature. Upon the optimized addition of DPP-H (0.75 wt%), the ionic conductivity was found to be improved to a maximum value of 0.393 mS·cm −1, and the highest diffusion coefficient of 1.02 × 10 −6 cm 2 s −1 was observed. The optimized GPEs photovoltaic characterization studies showed higher power conversion efficiency (PCE) of 6.69% for DSSC under light illumination intensity of 100 mW cm −2 . The same was compared with pure electrolyte, which delivered PCE of 4.39%. To gain an in-depth understanding of the interfacial resistance of the fabricated devices, the electron lifetime and transient photo response was analyzed. These above studies showed that prepared GPE could be an efficient alternative for traditional DSSCs with liquid electrolyte.